A TiO2-based bioprobe enabling excellent SERS activity in the detection of diverse circulating tumor cells. Issue 20 (27th April 2022) - Xu, Yanping; Lin, Jie; Wu, Xiaoxia; Xu, Xiawei; Zhang, Dinghu; Xie, Yujiao; Pan, Ting; He, Yiwei; Wu, Aiguo; Shao, Guoliang
Abstract : The designed TiO2 -based SERS bioprobe can be effectively utilized in detecting 4 diverse types of cancer cells in rabbit blood, which shows good sensitivity of the SERS detection technology. Abstract : Circulating tumor cells (CTCs) can be the seeds of tumor metastasis and are closely linked to cancer-related death. Fast and effective detection of CTCs is important for the early diagnosis of cancer and the evaluation of micrometastasis. However, the extreme rarity and heterogeneity of CTCs in peripheral blood make sensitive detection of CTCs a big challenge. In this paper, a TiO2 -based surface-enhanced Raman scattering (SERS) bioprobe is reported for the first time with outstanding ultrasensitive specificity, excellent stability of the signal, and good biocompatibility for the detection of CTCs. The TiO2 NPs were encoded with alizarin red (AR) and functionalized with reduced bovine serum protein (rBSA) and folic acid (FA). The limit of detection (LOD) for 4-mercaptobenzoic acid (4-MBA) and AR molecules adsorbed on the TiO2 SERS substrate is 5 × 10 −7 M. The designed TiO2 -based SERS bioprobe can be effectively utilized in detecting four diverse types of cancer cells in rabbit blood, which shows good sensitivity of the SERS detection technology. Finally, precise targeting of CTCs based on the SERS bioprobe with the function of fluorescence imaging is also confirmed by the fluorescence colouration test. This work offers a novel strategy for CTC detection and the development of non-noble metal semiconductor-based SERS platforms for tumor diagnosis.